Hap and Leonard [videorecording (DVD)] - Purefoy, James, 1964-; Williams, Michael Kenneth; Simpson, Jimmi; Lansdale, Joe R., 1951- (Anchor Bay Entertainment, 2017)
Based on the novels by Joe R. Lansdale, the six-hour series event follows Hap Collins, an East Texas white boy with a weakness for Southern women, and Leonard Pine, a gay, black Vietnam vet with a hot temper. When Hap's seductive ex-wife Trudy resurfaces with a deal they can't refuse, a simple get-rich-quick scheme snowballs into bloody mayhem.